Safety and efficacy of the pan-FGFR inhibitor erdafitinib in advanced urothelial carcinoma and other solid tumors: A systematic review and meta-analysis - Zheng, Xinyi; Wang, Hang; Deng, Junyue; Yao, Minghe; Zou, Xiuhe; Zhang, Fan; Ma, Xuelei (Frontiers in Oncology, 2023)
Objective: This review aimed to comprehensively analyze the safety and efficacy of erdafitinib in treating advanced and metastatic urothelial carcinoma and other solid tumors. Methods: PubMed, Embase, and ClinicalTrials.gov, were searched until 10th Feb 2022. The safety outcome as adverse events, and efficacy outcomes, including objective response rate, stable disease rates and progressive disease rates, were selected and analyzed by comprehensive meta-analysis version 3.0 and STATA 15.0. Results: The most common all-grade adverse events were hyperphosphatemia, dry mouth, stomatitis, diarrhea, and dysgeusia. The occurrence of ≥3 adverse events was relatively low, and stomatitis and hyponatremia were the most common. Moreover, eye disorders could not be ignored. Efficacy in urothelial carcinoma patients was obviously better than in other solid tumors patients, with a higher objective response rate (0.38 versus 0.10) and lower progressive disease rate (0.26 versus 0.68). All responses occurred in patients with fibroblast growth factor receptor (FGFR) alteration. In those patients, a specific FGFR alteration (FGFR3-TACC3) was observed to have a maximum response. Conclusion: Erdafitinib has satisfactory clinical activity for metastatic urothelial carcinoma and other solid tumors, while the toxicity is acceptable. With more RCTs and combination therapy trials published, erdafitinib will be applied widely.